Analisis Kelayakan Finansial dan Tahapan Business Life Cycle Usaha Peternakan Ayam Broiler Sun Farm - Febrinadia, Aulia Isnaini Widya; Yektiningsih, Endang; Tondang, Ika Sari (Universitas Bengkulu, 2025)
Sun Farm broiler farm is a broiler operation using a close-house, cage-type system that implements an all-in-all-out production model with a large broiler capacity. This study aims to: 1) analyze the amount of costs, revenue and income in the Sun Farm broiler farm business, 2) analyze the financial feasibility of the Sun Farm broiler farm business, and 3) analyze the stages of the business life cycle in the Sun Farm broiler farm business. This study was conducted at Sun Farm, a broiler farm that operates a closed-house cage system and an all-in-all-out production method, to provide a comprehensive understanding of its financial performance and business life cycle. Purposive sampling was employed to ensure that the selected location and informants were highly relevant to the research objectives, thereby facilitating the collection of accurate and meaningful data. Five informants were carefully selected based on specific criteria, and data were gathered using a combination of questionnaires, interviews, and documentation to capture both quantitative and qualitative aspects of the business. The analysis focused on three main objectives: first, to assess the costs, revenue, and income of the Sun Farm broiler business; second, to evaluate the financial feasibility using indicators such as Net Present Value (Rp 1,408,592,651), Benefit/Cost Ratio (0.187), Internal Rate of Return (20%), Return on Investment (8.9%), Break Even Point (production of 420,503 Kg for Rp 16,788/Kg), and Payback Period (3 years), all of which indicate that the business is financially viable; and third, to examine the stages of the business life cycle, where a sales growth of 11% shows that the business is currently in the growth stage. In conclusion, this study demonstrates that the Sun Farm broiler business is not only profitable but also strategically positioned for continued growth, and the chosen methods ensured reliable, in-depth insights into both its financial performance and developmental stage.